THE INCIDENCE OF IN-HOSPITAL HYPOGLYCEMIA AND ITS ASSOCIATED RISK FACTORS AMONG ADULT FILIPINO PATIENTS WITH DIABETES MELLITUS IN CHONG HUA HOSPITAL - Duyongco-Tiu, Ma. Vircel; Lagula-Bilocura, Imelda (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION This study will look into the occurrence of hypoglycemia in the Philippines as its increasing prevalence has been noted. METHODOLOGY All nonpregnant, adult, Filipino patients, admitted and discharged from January 2015 to June 2015 were identified. The primary outcome was to determine the incidence of hypoglycemia, severity of hypoglycemia, the patients’ dietary status, medication, and the common hospital area of the hypoglycemic event. Their clinical profile was also analyzed. The secondary outcome was to determine the occurrence of congestive heart failure (CHF), fatal/nonfatal myocardial infarction (MI), fatal/nonfatal cerebrovascular disease (CVD), and all-cause mortality during the admission of patients with hypoglycemia. RESULTS Among the 1676 patients with diabetes, 8.9% had the nonsevere type (BG 51-69 mg/dL) hypoglycemia. Age >65 (52.7% vs 36.2%, p<0.001), diabetes duration for more than 8.56 years±10.34 years, the presence of cardiovascular disease (62.7% vs 48.6%, p<0.001), CHF (8.7% vs 4.4%, p=0.009) and stage III, IV, V kidney diseases (32.7% vs 25.1%, p=0.043, 12% vs 5.5%, p=0.002, 12% vs 4.1%, p<0.001, respectively), being on tube feeding (8% vs 2.6%, p<0.01) or on nothing per orem (8% vs 2%, p<0.001), and the use of insulin whether combined with oral therapy (25.3% vs 16.5%, p<0.006) or used alone (34.7% vs 12.1%, p<0.001) were the associated risk factors. Non-ICU ward had more hypoglycemia events (82.7%). Only 1 patient had MI, 1 had CVD, and 1 had CHF. The all-cause mortality rate was 4.7%. CONCLUSION The hypoglycemia incidence of 8.9% should be addressed by being cautious among patients with risk factors.